HOW WORK CULTURE EFFECTS ON EMPLOYEE PERFORMANCE DURING THE COVID-19 PANDEMIC : A QUANTITATIVE ANALYSIS - Rahadian, Fajar; Zulkarnaen, Wandy (2021)
The occurrence of the COVID-19 pandemic has an impact on changing work patterns from face-to-face to work from home. The purpose of the study was to examine the effect of work culture on performance. The method in this study uses quantitative. Data processing uses simple regression analysis to process data with the help of SPSS. It is known that the significance value of the work culture variable on performance is 0.000 <0.05 and the t value is 4.528> 2.022. Thus the first hypothesis is accepted, which means that there is an influence of work culture on the performance of Bandung City Population and Civil Registration Service Employees during the COVID-19 Pandemic Period.